KAUSALITAS VARIABEL KELAPA SAWIT DAN KERUSAKAN LINGKUNGAN HIDUP DI INDONESIA (PENDEKATAN PAIRWISE GRANGER CAUSALITY TESTS) - Syahril Syahril; Arie Saputra; Irmayani Irmayani (JURNAL EKOMBIS, 2020)
The study used the monthly time series data in the period from January 2008 to December 2017, with the number of observations being 120 months. This study analyzes causality relationships between variables using the Vector Error Correction Model (VECM) approach of Pairwise Granger Causality Tests. The results showed that Indonesia's CPO price has the causality of one Indonesia's environmental quality index. Then the same results also variable the price of the world CPO has the causality of a quality index of Indonesian environment, this means that the variable change price of CPO world Cederung increase production by expanding oil plantation area. Expansion of oil palm plantations lowers the environmental quality index and ultimately undermine the Indonesian environment.Keywords: CPO Price, Pairwise Granger Causality test, VECM